Redistribution of Extracellular Superoxide Dismutase Causes Neonatal Pulmonary Vascular Remodeling and PH but Protects Against Experimental Bronchopulmonary Dysplasia - Laurie G. Sherlock; Ashley Trumpie; Laura Hernandez-Lagunas; Sarah McKenna; Susan Fisher; Russell Bowler; Clyde J. Wright; Cassidy Delaney; Eva Nozik-Grayck (MDPI AG, 2018)
Background: A naturally occurring single nucleotide polymorphism (SNP), (R213G), in extracellular superoxide dismutase (SOD3), decreases SOD3 matrix binding affinity. Humans and mature mice expressing the R213G SNP exhibit increased cardiovascular disease but decreased lung disease. The impact of this SNP on the neonatal lung at baseline or with injury is unknown. Methods: Wild type and homozygous R213G mice were injected with intraperitoneal bleomycin or phosphate buffered saline (PBS) three times weekly for three weeks and tissue harvested at 22 days of life. Vascular and alveolar development were evaluated by morphometric analysis and immunostaining of lung sections. Pulmonary hypertension (PH) was assessed by right ventricular hypertrophy (RVH). Lung protein expression for superoxide dismutase (SOD) isoforms, catalase, vascular endothelial growth factor receptor 2 (VEGFR2), endothelial nitric oxide synthase (eNOS) and guanosine triphosphate cyclohydrolase-1 (GTPCH-1) was evaluated by western blot. SOD activity and SOD3 expression were measured in serum. Results: In R213G mice, SOD3 lung protein expression decreased, serum SOD3 protein expression and SOD serum activity increased compared to wild type (WT) mice. Under control conditions, R213G mice developed pulmonary vascular remodeling (decreased vessel density and increased medial wall thickness) and PH; alveolar development was similar between strains. After bleomycin injury, in contrast to WT, R213G mice were protected from impaired alveolar development and their vascular abnormalities and PH did not worsen. Bleomycin decreased VEGFR2 and GTPCH-1 only in WT mice. Conclusion: R213G neonatal mice demonstrate impaired vascular development and PH at baseline without alveolar simplification, yet are protected from bleomycin induced lung injury and worsening of pulmonary vascular remodeling and PH. These results show that vessel bound SOD3 is essential in normal pulmonary vascular development, and increased serum SOD3 expression and SOD activity prevent lung injury in experimental bronchopulmonary dysplasia (BPD) and PH.